Caminhos da Espiritualidade: o cuidar e o cuidar-se no trabalho em saúde (RECIIS, 2015)
VASCONCELOS, Eymard Mourão (Org.) et al. A espiritualidade no trabalho em saúde. São Paulo: Editora Hucitec, 2006, 391p. ISBN: 85-271-0689-2